Practice to pitch: The relationship between force-velocity profiles and match-day performance of semi-professional rugby union players - Heather, Ormond; Lander, Patrick; Rayner, Russell (Frontiers in Sports and Active Living, 2023)
Introduction This exploratory study aimed to assess the relationship between athlete neuromuscular performance and rugby performance indicators. Specifically, the study looked at the force-velocity profiles (FVPs) derived from four common resistance exercises and their relationship with rugby performance indicators (RPIs). Methods The study recruited twenty-two semi-professional male rugby players (body mass 102.5 ± 12.6 kg, height 1.85 ± 0.74 m, age 24.4 ± 3.4 years) consisting of ten backs and twelve forwards. Prior to the first game of a Covid-impacted nine-match season, participants performed four common resistance exercises (barbell box squat, jammer push-press, sled pull, and sled push) at incremental loads to establish force-velocity profiles. During the season, rugby performance indicators (post-contact metres, tries, turnovers conceded, tackles, try assists, metres ran, defenders beaten, and tackle breaks) were collated from two trusted sources by a performance analyst. Correlational analyses were used to determine the relationship between the results of FVPs and RPIs. Results The study found a statistically significant, moderate, positive correlation between tackle-breaks and sled push V0 (r = .35, p = .048). Significant, large, positive correlations were also found between tackles and jammer push-press V0 (r = .53, p = .049) and tackle-breaks and sled pull F0 (r = .53, p = .03). There was a significant, negative relationship between sled pull V0 and tackle-breaks (r = −.49, p = .04). However, the largest, significant correlation reported was between metres ran and sled pull F0 (r = .66, p = .03). Conclusion The study suggests that a relationship may exist between FVPs of particular exercises and RPIs, but further research is required to confirm this. Specifically, the results suggest that horizontal resistance training may be best to enhance RPIs (tackle-breaks, tackles, and metres ran). The study also found that maximal power was not related to any rugby performance indicator, which suggests that a specified prescription of either force or velocity dominant exercises to enhance RPIs may be warranted.